Review of sustainability of average Nepalese subsistence farm in mid-hills of Nepal - Chaulagai, Tilak R (Journal of Agriculture and Environment, 2014)
The main aim of this paper is to depict the sustainability condition of an average subsistence farm in the mid-hill condition of Nepal. For the purpose, a hypothetical farm representing the average condition of the farming system in the area is taken. The analysis is based on the secondary information. For the purpose, only few indicators for the sustainability are analysed including gross profit margin, nitrogen use efficiency and nitrogen balance. The results reflect that an average subsistence farm in the midhill of Nepal earn just NRs 79,449 per annum. The nitrogen balance was negative and nitrogen use efficiency was more than 100% reflecting the system was economically and environmentally unsustainable. The problem behind unsustainability of the system is basically related with poverty and increased population pressure on poorly fertile land. Only a joint venture of public and private sector can address the problem.